A contribuição da poesia na formação de leitores do ensino fundamental - BARBOSA, Thamires do Socorro (2020)
This study intends promote a reflection about the contribution of the poetry in the formation process of reader’s in the Elementary School. Presenting the concepts of poetry, reading and readers formation, we will understand how the poetry, indeed, contribute in the formation process of the student reader. For this, we will make a dialogue with some authors who treated directly or indirectly about this theme, such as: Magda Soares (2006), Marisa Lajolo, Regina Zilberman (1995, 1998), Paul Zumthor(1993, 2007, 2010), Maria Cunha (2003) and Vigotsky(2004, 2007, 2014).